Optical fiber image transmitting element for high-resolution X-ray detection and preparation method and application of optical fiber image transmitting element

By forming a microporous structure at the core of the optical fiber image transmission element and filling it with perovskite quantum dot glass powder, combined with the setting of the protective layer, the problem of insufficient detection efficiency and resolution of the existing X-ray detector is solved, and efficient and high-resolution X-ray detection effect is achieved.

CN119717124AActive Publication Date: 2025-03-28CHINA BUILDING MATERIALS ACADEMY CO LTD +1

Patent Information

Application Number
CN202411624585.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-03-28
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

The detection efficiency and resolution of existing X-ray detectors have not yet met the needs of improved detection, and it is difficult to meet the high standards requirements in the fields of national defense, civil and scientific research.

Method used

A high-resolution X-ray detection optical fiber image transmission element is used, which forms a microporous structure by pickling at the core of the optical fiber image transmission element, and fills the perovskite quantum dot glass powder into these microporous structures, and finally a protective layer is provided at the filling surface.

Benefits of technology

It achieves high luminous intensity and long-term stability, improves detection efficiency and detection resolution, and efficiently emits a single optical fiber, effectively improving detection resolution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119717124A_ABST
    Figure CN119717124A_ABST
Patent Text Reader

Abstract

The invention provides an optical fiber image transmitting element for high-resolution X-ray detection and a preparation method and application thereof, and the preparation method of the optical fiber image transmitting element for high-resolution X-ray detection comprises the steps: carrying out the acid pickling of the cross section of one end of the optical fiber image transmitting element, enabling the cross section to form a microporous structure with the depth of 100-500 [mu] m, obtaining a pickled optical fiber image transmitting element; wherein a fiber core of the optical fiber image transmission element is made of an easily acid-etching material, and a cladding is made of an acid-etching-resistant material; filling perovskite quantum dot glass powder into the microporous structure to obtain a filled optical fiber image transmitting element; and arranging a protective layer on the filling surface of the filling optical fiber image transmitting element to obtain the high-resolution optical fiber image transmitting element for X-ray detection. The prepared high-resolution optical fiber image transmitting element for X-ray detection has the advantages of high brightness and high resolution, the detection efficiency and detection resolution of an X-ray detector are effectively improved, and the high-resolution optical fiber image transmitting element has important significance in the fields of national defense, civil use and scientific research.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of X-ray detection, and in particular to an optical fiber imaging element for high-resolution X-ray detection and a preparation method and application thereof. Background Art

[0002] X-rays are a type of electromagnetic wave with a short wavelength ranging from 0.01nm to 10nm and an energy of 100eV to 10MeV. Based on the penetration, differential absorption, photosensitivity and fluorescence effects of X-rays, they can be widely used in environmental monitoring, geophysical detection, radiotherapy and medical diagnosis. Due to the rapid development of X-ray applications, higher demands have been placed on X-ray detection technology.

[0003] At present, the detection efficiency and resolution of X-ray detectors need to be improved. Therefore, how to improve the detection efficiency and detection resolution of X-ray detectors is of great significance to the fields of national defense, civil use and scientific research. Summary of the invention

[0004] The main purpose of the present invention is to provide a fiber optic imaging element for high-resolution X-ray detection and its preparation method and application. The technical problem to be solved is how to improve the detection efficiency and detection resolution of the X-ray detector so as to make it more suitable for practical use.

[0005] The purpose of the present invention and the technical problem to be solved are achieved by adopting the following technical solutions. According to the method for preparing a high-resolution X-ray detection optical fiber image transmission element proposed by the present invention, the steps include:

[0006] Acid-washing is performed on the cross section of one end of the optical fiber imaging element to form a microporous structure at the cross section, the depth of the microporous structure is 100 to 500 μm, and an acid-washed optical fiber imaging element is obtained; the core of the optical fiber imaging element is made of an acid-easy material, and the cladding is made of an acid-resistant material;

[0007] Filling the perovskite quantum dot glass powder into the aforementioned microporous structure to obtain a filled optical fiber imaging element; and,

[0008] A protective layer is provided on the filling surface of the aforementioned filled optical fiber imaging element to obtain an optical fiber imaging element for high-resolution X-ray detection.

[0009] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures.

[0010] In some embodiments, according to the aforementioned method for preparing an optical fiber imaging element for high-resolution X-ray detection, the aforementioned perovskite quantum dot glass powder is CsPbX3 perovskite quantum dot glass powder; wherein X is at least one of Cl, Br and I.

[0011] In some embodiments, according to the aforementioned method for preparing an optical fiber imaging element for high-resolution X-ray detection, the components of the aforementioned CsPbX3 perovskite quantum dot glass powder, measured in terms of oxide mass percentage, include: SiO2: 30-40%; H3BO3: 20-30%; ZnO: 15-20%; Cs2CO3: 10-15%; PbX2: 5-10%; and, NaX: 5-10%.

[0012] In some embodiments, according to the aforementioned method for preparing the optical fiber imaging element for high-resolution X-ray detection, the aforementioned method for preparing the CsPbX3 perovskite quantum dot glass powder comprises the following steps:

[0013] preparing glass raw materials, melting the aforementioned glass raw materials at 1000-1100° C. to obtain a glass melt;

[0014] pouring the aforementioned molten glass into a mold to obtain a precursor glass;

[0015] The aforementioned precursor glass is annealed at 350-450° C. for 2-3 hours to obtain CsPbX3 perovskite quantum dot glass; and,

[0016] The aforementioned CsPbX3 perovskite quantum dot glass is ground into powder to obtain the aforementioned CsPbX3 perovskite quantum dot glass powder.

[0017] In some embodiments, according to the aforementioned method for preparing an optical fiber imaging element for high-resolution X-ray detection, the method of filling the aforementioned perovskite quantum dot glass powder into the aforementioned microporous structure comprises the following steps:

[0018] a. dispersing the aforementioned perovskite quantum dot glass powder in an organic solvent to obtain a quantum dot dispersion;

[0019] b. immersing the aforementioned microporous structure of the aforementioned pickled optical fiber imaging element in the aforementioned quantum dot dispersion, ultrasonically treating, then taking out the aforementioned pickled optical fiber imaging element, scraping off the aforementioned quantum dot dispersion on the surface without pores, and drying;

[0020] Repeat step b multiple times until the aforementioned perovskite quantum dot glass powder fully fills the aforementioned microporous structure to obtain the aforementioned filled optical fiber imaging element.

[0021] In some embodiments, according to the aforementioned method for preparing an optical fiber imaging element for high-resolution X-ray detection, the size of the aforementioned perovskite quantum dot glass powder is 100 to 200 nm.

[0022] In some embodiments, according to the aforementioned method for preparing an optical fiber imaging element for high-resolution X-ray detection, the aforementioned protective layer includes a quartz window, and the thickness of the aforementioned quartz window is 2 to 3 mm.

[0023] In some embodiments, according to the aforementioned method for preparing an optical fiber imaging element for high-resolution X-ray detection, the aforementioned protective layer includes an anti-reflection film.

[0024] The purpose of the present invention and the technical problem solved by the present invention are also achieved by adopting the following technical solutions. According to the present invention, a high-resolution X-ray detection optical fiber image transmission element is provided, which comprises:

[0025] An optical fiber imaging element, wherein the core of the optical fiber imaging element is made of an acid-resistant material, the cladding is made of an acid-resistant material, the core of the optical fiber imaging element is concave at a cross section at one end, and a microporous structure with a depth of 100 to 500 μm is formed at the cross section;

[0026] Perovskite quantum dot glass powder, the aforementioned perovskite quantum dot glass powder is filled in the aforementioned microporous structure; and,

[0027] A protective layer, wherein the protective layer is arranged on the cross section of the optical fiber imaging element filled with the perovskite quantum dot glass powder.

[0028] The purpose of the present invention and the technical problems solved therein are also achieved by adopting the following technical solutions: According to the present invention, an application of the above-mentioned high-resolution X-ray detection optical fiber image transmission element in the field of X-ray detection is proposed.

[0029] Through the above technical solution, the optical fiber image transmission element for high-resolution X-ray detection and its preparation method and application of the present invention have at least the following advantages:

[0030] The preparation method of the optical fiber image transmission element for high-resolution X-ray detection proposed in the present invention adopts an optical fiber image transmission element with a core made of an acid-resistant material and a cladding made of an acid-resistant material, realizes a high-precision, high-uniform and regularly arranged microporous structure on the cross section of the optical fiber image transmission element based on the acid washing method, controls the depth of the microporous structure to be 100-500 μm, and uses perovskite quantum dot glass powder to fill the microporous structure. The perovskite quantum dot glass powder has a high photoluminescence quantum yield, excellent color purity and an adjustable band gap, and controls its filling thickness to be 100-500 μm, so that it acts as a photosensitive material for absorbing X-rays, which can achieve high luminescence intensity and long-term stability, and improve detection efficiency and detection life. At the same time, after filling the perovskite quantum dot glass powder, a single optical fiber can be efficiently luminesced, effectively improving the detection resolution; the light converted by the quantum dot material in the microporous structure after X-ray irradiation is transmitted by the corresponding optical fiber, and each optical fiber is a separate image transmission unit. Compared with the diffuse reflection light of the stimulated emission of the traditional quantum dot material, the resolution is greatly improved. The optical fiber image transmission element for high-resolution X-ray detection prepared by the present invention has the advantages of high brightness and high resolution, effectively improving the detection efficiency and detection resolution of the X-ray detector, and is of great significance to the fields of national defense, civil use and scientific research.

[0031] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 It is a schematic structural diagram of the optical fiber imaging element for high-resolution X-ray detection disclosed in Example 1 of the present invention;

[0033] Figure 2 is a schematic structural diagram of an optical fiber imaging element for high-resolution X-ray detection disclosed in Example 2 of the present invention;

[0034] Figure 3 is a schematic structural diagram of an optical fiber imaging element for high-resolution X-ray detection disclosed in Example 3 of the present invention;

[0035] Figure 4 It is a graph of the X-ray radiation luminescence spectrum of the quantum dot glass film quartz plate and the optical fiber imaging element for high-resolution X-ray detection in Example 1 of the present invention;

[0036] Figure 5 It is a graph of the X-ray radiation luminescence spectrum of the quantum dot glass film quartz plate and the optical fiber imaging element for high-resolution X-ray detection in Example 2 of the present invention;

[0037] Figure 6It is a graph of the X-ray radiation luminescence spectrum of the quantum dot glass film quartz plate and the optical fiber imaging element for high-resolution X-ray detection in Example 3 of the present invention;

[0038] Figure 7 It is a graph of the X-ray radiation luminescence spectrum of the quantum dot glass film quartz plate and the optical fiber imaging element for high-resolution X-ray detection in Example 4 of the present invention;

[0039] Figure 8 It is a graph of the X-ray radiation luminescence spectrum of the quantum dot glass film quartz plate and the optical fiber imaging element for high-resolution X-ray detection in Example 5 of the present invention;

[0040] Fig. 9 This is an X-ray diffraction test diagram of CsPbBr3 quantum dots in Example 1 of the present invention.

[0041] Description of reference numerals:

[0042] 1. Quartz window; 2. Alumina and hafnium oxide composite film; 3. CsPbBr3 perovskite quantum dot glass powder; 4. Acid-washed optical fiber panel; 5. Acid-washed optical fiber light cone; 6. Acid-washed optical fiber image inverter. DETAILED DESCRIPTION

[0043] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the following is a detailed description of a high-resolution X-ray detection optical fiber image transmission element and its preparation method and application according to the present invention, its specific implementation, structure, features and effects, in combination with the accompanying drawings and preferred embodiments. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures or characteristics in one or more embodiments may be combined in any suitable form.

[0044] The present invention provides these embodiments to make the present invention thorough and complete, and fully express the scope of the present invention to those skilled in the art. It should be noted that unless otherwise specifically stated, the relative arrangement of the parts and steps, the composition of materials, numerical expressions and numerical values ​​set forth in these embodiments should be interpreted as being merely exemplary, rather than as limiting.

[0045] The present invention provides a method for preparing a fiber optic imaging element for high-resolution X-ray detection, such as Figures 1 to 3 As shown, the steps include:

[0046] Acid-washing is performed on the cross section of one end of the optical fiber imaging element to form a microporous structure at the cross section, the depth of the microporous structure is 100 to 500 μm, and an acid-washed optical fiber imaging element is obtained; the core of the optical fiber imaging element is made of an acid-easy material, and the cladding is made of an acid-resistant material;

[0047] Filling the perovskite quantum dot glass powder into the aforementioned microporous structure to obtain a filled optical fiber imaging element; and,

[0048] A protective layer is provided on the filling surface of the aforementioned filled optical fiber imaging element to obtain an optical fiber imaging element for high-resolution X-ray detection.

[0049] Specifically, the optical fiber image transmission element can be selected from an optical fiber panel, an optical fiber light cone or an optical fiber image invertor. Based on the acid resistance of the core and the cladding, the acid solution used for pickling can be selected from at least one of 0.1-3.0 mol / L hydrochloric acid, nitric acid, citric acid and sulfuric acid. The pickling method can produce a regularly arranged microporous structure with holes only at the core position. This method can accurately prepare micropores at the core position without destroying the cladding structure to cause optical crosstalk. In addition, the diameter of the micropores is controlled by adjusting the diameter of the fiber core, and the depth of the micropores is controlled by adjusting the acid concentration and immersion time, so as to achieve a high-precision, high-uniform regularly arranged micropore structure with adjustable micropore diameter and depth.

[0050] Perovskite quantum dot glass powder has high photoluminescence quantum yield, excellent color purity and adjustable band gap. By controlling the depth of the microporous structure to 100-500μm and the filling thickness to 100-500μm, it can act as a photosensitive material that absorbs X-rays, achieving high luminescence intensity and long-term stability, and improving detection efficiency and detection life. At the same time, after filling the perovskite quantum dot glass powder, a single optical fiber can be efficiently luminous, effectively improving the detection resolution; the light converted by the perovskite quantum dot glass powder in the microporous structure after X-ray irradiation is transmitted by the corresponding optical fiber, and each optical fiber is a separate image transmission unit. Compared with the diffuse reflection light of stimulated emission of traditional quantum dot materials, the resolution is greatly improved. Perovskite quantum dot glass powder can be made of materials commonly used in the field, and inorganic or organic perovskite quantum dot glass can be used. Inorganic perovskite quantum dot glass is preferred; compared with organic perovskite quantum dot glass, inorganic perovskite quantum dot glass has better stability and is suitable for a wider range of environments. Preferably, the size of the perovskite quantum dot glass is 100-200 nm. The perovskite quantum dot glass powder can be filled by physical deposition or direct filling, etc., which is not limited here.

[0051] The protective layer can protect the filled perovskite quantum dot glass powder from being polluted and falling off, isolate water and oxygen, extend the service life, and expand the scope of use. The protective layer can be made of transparent materials such as quartz, organic glass, and resin.

[0052] The high-resolution X-ray detection optical fiber image transmission element prepared by the method of the present invention has the advantages of high brightness and high resolution, effectively improving the detection efficiency and detection resolution of the X-ray detector, and is of great significance to the fields of national defense, civil use and scientific research.

[0053] In some embodiments, the aforementioned perovskite quantum dot glass powder is CsPbX3 perovskite quantum dot glass powder; wherein X is at least one of Cl, Br and I.

[0054] Specifically, CsPbX3 perovskite quantum dot glass has high hardness, good stability and high transmittance, making the prepared optical fiber image transmission element brighter and suitable for a wider range of environments. At the same time, by combining the three ions of Cl, Br and I, perovskite quantum dot materials that emit visible light of any wavelength can be prepared.

[0055] In some embodiments, the components of the aforementioned CsPbX3 perovskite quantum dot glass powder include, by oxide mass percentage: SiO2: 30-40%; H3BO3: 20-30%; ZnO: 15-20%; Cs2CO3: 10-15%; PbX2: 5-10%; and, NaX: 5-10%.

[0056] In some embodiments, the method for preparing the aforementioned CsPbX3 perovskite quantum dot glass powder comprises the following steps:

[0057] preparing glass raw materials, melting the aforementioned glass raw materials at 1000-1100° C. to obtain a glass melt;

[0058] pouring the aforementioned molten glass into a mold to obtain a precursor glass;

[0059] The aforementioned precursor glass is annealed at 350-450° C. for 2-3 hours to obtain CsPbX3 perovskite quantum dot glass; and,

[0060] The aforementioned CsPbX3 perovskite quantum dot glass is ground into powder to obtain the aforementioned CsPbX3 perovskite quantum dot glass powder.

[0061] Specifically, in the CsPbX3 perovskite quantum dot glass prepared by the method proposed in the present invention, the outer ring of each perovskite grain is wrapped by an amorphous glass component, which effectively avoids contact with water and oxygen and improves the long-term stability of the perovskite quantum dots. By heating the precursor glass at 350-450°C for 2-3h to anneal, CsPbX3 can be induced to grow in situ in the glass matrix. The CsPbX3 perovskite quantum dot glass can be ground using the conventional techniques in the art. For example, the CsPbX3 perovskite quantum dot glass is placed in a ball mill, the rotation speed is adjusted to 400-500rpm, and the time is 5-6h, and a CsPbX3 perovskite quantum dot glass powder with a size of 100-200nm can be obtained.

[0062] In some embodiments, the method of filling the aforementioned perovskite quantum dot glass powder into the aforementioned microporous structure comprises the following steps:

[0063] a. dispersing the aforementioned perovskite quantum dot glass powder in an organic solvent to obtain a quantum dot dispersion;

[0064] b. immersing the aforementioned microporous structure of the aforementioned pickled optical fiber imaging element in the aforementioned quantum dot dispersion, ultrasonically treating, then taking out the aforementioned pickled optical fiber imaging element, scraping off the aforementioned quantum dot dispersion on the surface without pores, and drying;

[0065] Repeat step b multiple times until the aforementioned perovskite quantum dot glass powder fully fills the aforementioned microporous structure to obtain the aforementioned filled optical fiber imaging element.

[0066] Specifically, the method for filling perovskite quantum dot glass powder is convenient to operate, and the powder is filled evenly and compactly, and is not easy to fall off. Preferred are volatile, low-toxic organic solvents, such as acetone, anhydrous ethanol or isopropanol. The method of dispersing the powder in the organic solvent can be mechanical stirring, shaking or ultrasound. For example, the perovskite quantum dot glass powder is evenly dispersed in an acetone solvent by ultrasound for 30-50 minutes, the pickled optical fiber imaging element is immersed in the quantum dot dispersion for ultrasonic treatment for 30-50 minutes, and then the pickled optical fiber imaging element is pulled out of the quantum dot dispersion at a speed of 1-3mm / s, and the quantum dot dispersion at the non-porous position on the surface is scraped off with a scraper, and then placed in an oven at 50-70°C for 10-20 minutes to fill the quantum dot glass powder in the microporous structure, and repeated many times until the perovskite quantum dot glass powder fills the microporous structure.

[0067] In some embodiments, the size of the aforementioned perovskite quantum dot glass powder is 100-200 nm.

[0068] Specifically, the size of the perovskite quantum dot glass powder is less than 100nm, and too many perovskite grains are exposed, which affects the long-term stability of the perovskite quantum dots; the size of the perovskite quantum dot glass powder is greater than 200nm, which affects the resolution. Therefore, the size of the perovskite quantum dot glass powder is controlled at 100-200nm.

[0069] In some embodiments, the aforementioned protective layer includes an anti-reflection film.

[0070] Specifically, setting an anti-reflection film can further increase the brightness of the optical fiber imaging element. The anti-reflection film can be an aluminum oxide and hafnium oxide composite film 2. The aluminum oxide and hafnium oxide composite film 2 has the advantages of high hardness and high transmittance. For example, the film system structure of the aluminum oxide and hafnium oxide composite film 2 and the thickness of each film layer are: HfO2 (115-118nm)-Al2O3 (70-72nm)-HfO2 (120-122nm)-Al2O3 (40-42nm)-HfO2 (72-74nm)-Al2O3 (80-82nm)-filled optical fiber imaging element.

[0071] In some embodiments, the aforementioned protective layer includes a quartz window 1 , and the thickness of the aforementioned quartz window 1 is 2 to 3 mm.

[0072] Specifically, when the protective layer includes both an anti-reflection film and a quartz window 1, the protective layer is installed as follows: an anti-reflection film is plated on the filling surface of the optical fiber imaging element, and then the anti-reflection film and the surface of the quartz window 1 are polished to control the roughness to 5-10 nm, and then the quartz window 1 is placed on the surface of the anti-reflection film, and heated to increase the activation energy of the molecules and atoms on the surface of the anti-reflection film and the protective layer, so that the two are bonded as a whole. Preferably, the heating temperature is 200-250°C.

[0073] The present invention provides an optical fiber imaging element for high-resolution X-ray detection, which comprises:

[0074] An optical fiber imaging element, wherein the core of the optical fiber imaging element is made of an acid-resistant material, the cladding is made of an acid-resistant material, the core of the optical fiber imaging element is concave at a cross section at one end, and a microporous structure with a depth of 100 to 500 μm is formed at the cross section;

[0075] Perovskite quantum dot glass powder, the aforementioned perovskite quantum dot glass powder is filled in the aforementioned microporous structure; and,

[0076] A protective layer, wherein the protective layer is arranged on the cross section of the optical fiber imaging element filled with the perovskite quantum dot glass powder.

[0077] The present invention proposes an application of the above-mentioned high-resolution X-ray detection optical fiber imaging element in the field of X-ray detection. For example, the high-resolution X-ray detection optical fiber imaging element proposed by the present invention can be installed on an X-ray detector for use.

[0078] The present invention will be further described below in conjunction with specific embodiments, but this should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technicians in this field based on the above-mentioned contents of the present invention still fall within the scope of protection of the present invention.

[0079] Unless otherwise specified, the materials, reagents, etc. involved below are all commercially available products well known to those skilled in the art; unless otherwise specified, the methods described are all methods well known in the art. Unless otherwise defined, the technical terms or scientific terms used should have the common meanings understood by ordinary technicians in the field to which the present invention belongs.

[0080] In the following embodiments, the core of the optical fiber imaging element is made of an acid-etchable material. In terms of oxide molar percentage, the core components include: SiO2: 30.3-36.4%; B2O3: 18.9-20.2%; La2O3: 5.9-6.1%; the total content of BaO and CaO is: 33.7-39.4%; Al2O3: 1.6-2.3%; TiO2: 2.0-2.9%; the cladding of the optical fiber imaging element Acid-resistant materials are used, and the cladding components, calculated by molar percentage of oxides, include: SiO2: 70.5-74.5%; PbO: 12.0-12.5%; Bi2O3: 0-2.0%; the total content of Na2O, K2O, Rb2O and Cs2O is 5.8-7.7%; the total content of BaO and MgO is 4.6-6.7%; Al2O3: 1.1-3.0%; TiO2: 0-2.0%.

[0081] Embodiment 1:

[0082] This embodiment provides a high-resolution X-ray detection optical fiber image transmission element and a preparation method thereof. Figure 1 .

[0083] The optical fiber image transmission element in this embodiment uses an optical fiber panel with a core diameter of 10 μm and a thickness of 10 mm. The cross section of the optical fiber panel is immersed in a nitric acid solution with a volume of 1 L and a concentration of 0.5 mol / L for 48 hours, so that a regularly arranged microporous structure with a micropore diameter of 10 μm and a depth of 100 μm is formed at the cross section of the optical fiber panel, and an acid-washed optical fiber panel 4 is obtained.

[0084] The perovskite quantum dot glass powder in this embodiment is CsPbBr3 perovskite quantum dot glass powder 3 with a fluorescent color of yellow light. In terms of oxide mass percentage, the ratio of CsPbBr3 perovskite quantum dot glass is 30% SiO2; 30% H3BO3; 20% ZnO; 10% Cs2CO3; 5% PbBr2; 5% NaBr. About 10g of high-purity raw materials are fully mixed and melted in air at 1050°C for 12min to produce a uniform glass melt. The melt is then poured into a brass mold to obtain a precursor glass. Finally, the precursor glass is annealed by heating at 400°C for 2h to induce in-situ growth of CsPbBr3 in the glass matrix to obtain CsPbBr3 perovskite quantum dot glass. Put the CsPbBr3 perovskite quantum dot glass into a ball mill, adjust the rotation speed to 500 rpm, and the time to 5 hours to obtain CsPbBr3 perovskite quantum dot glass powder 3 with a size of 150 nm.

[0085] The CsPbBr3 perovskite quantum dot glass powder 3 is added to an acetone solvent and ultrasonicated for 30 minutes to uniformly disperse it to obtain a quantum dot dispersion. The acid-washed optical fiber panel 4 is immersed in the quantum dot dispersion, ultrasonicated for 30 minutes, and then the optical fiber panel is pulled out of the solution at a speed of 1 mm / s, and the quantum dot dispersion on the surface without holes is scraped off with a scraper, and then placed in an oven at 50°C for 10 minutes to dry, so that the CsPbBr3 perovskite quantum dot glass powder 3 is filled in the micropores; repeat several times until the quantum dot glass powder fills the micropores to obtain a filled optical fiber panel.

[0086] Aluminum oxide and hafnium oxide composite film 2 is plated on the filling surface of the filling optical fiber panel, and then a quartz window 1 with a thickness of 2 mm is placed on the surface of the anti-reflection film, and a temperature of 230°C is applied to activate the molecules and atoms on the surface of the quartz window 1 and the anti-reflection film, so that the two are bonded as a whole, and a high-resolution X-ray detection optical fiber imaging element is obtained. Among them, the film system structure of the aluminum oxide and hafnium oxide composite film 2 and the thickness of each film layer are:

[0087] Quartz window 1-HfO2 (115~118nm)-Al2O3 (70~72nm)-HfO2 (120~122nm)-Al2O3 (40~42nm)-HfO2 (72~74nm)-Al2O3 (80~82nm)-filled optical fiber faceplate.

[0088] 0.4 ml of the aforementioned quantum dot dispersion was dripped onto the surface of a quartz substrate with a thickness of 12 mm, and the rotation speed was controlled to 500 rpm and the time was 60 s by spin coating. After spin coating, the film was heated in an oven at 60° C. for 30 min. This process was repeated three times to form a quantum dot glass film with a thickness of 100 μm on the surface of the quartz substrate, thereby obtaining a quantum dot glass film quartz plate.

[0089] The prepared CsPbBr3 quantum dot glass was subjected to X-ray diffraction test, and the results are as follows: Fig. 9 As shown in the figure, it can be seen that the peaks correspond to those of the PDF standard comparison card, proving that high-purity CsPbBr3 quantum dots have been successfully synthesized.

[0090] The X-ray emission spectrum of the quantum dot glass film quartz plate and the high-resolution X-ray detection optical fiber imaging element in this embodiment was tested using the emission spectrum under the action of X-rays at 50 kV and 10 μA. The test results are shown in Figure 2. Figure 4 As shown, A is the luminous intensity curve of the quantum dot glass film quartz plate, and B is the luminous intensity curve of the optical fiber imaging element for high-resolution X-ray detection. The peak position of the quantum dot glass film quartz plate is at 530nm and the peak shape is sharp, and the relative luminous intensity is 100%. The peak position of the optical fiber imaging element for high-resolution X-ray detection is at 530nm and the peak shape is sharp, indicating that the luminous purity of the sample is high; the relative luminous intensity is 80%, and the luminous intensity is only lost by 20%, indicating that the luminous intensity of the sample is high. Using X-ray light as the light source to test the resolution of the optical fiber panel in this embodiment is 50.8lp / mm, and the resolution of the optical fiber imaging element for high-resolution X-ray detection is 50.8lp / mm, indicating that there is no loss of resolution when filling the quantum dot glass powder in the microporous structure.

[0091] Embodiment 2:

[0092] This embodiment provides a high-resolution X-ray detection optical fiber image transmission element, and its structural schematic diagram is shown in Figure 2 .

[0093] The difference between this embodiment and embodiment 1 is that the optical fiber image transmission element adopts an optical fiber light cone with a core diameter of 10 μm and a thickness of 10 mm. Furthermore, the pickled optical fiber panel 4 in embodiment 1 is an pickled optical fiber light cone 5 in this embodiment; the filled optical fiber panel in embodiment 1 is a filled optical fiber light cone in this embodiment.

[0094] The X-ray emission spectrum of the quantum dot glass film quartz plate and the high-resolution X-ray detection optical fiber imaging element in this embodiment was tested using the emission spectrum under the action of X-rays at 50 kV and 10 μA. The test results are shown in Figure 2. Figure 5As shown, A is the luminous intensity curve of the quantum dot glass film quartz plate, and B is the luminous intensity curve of the optical fiber imaging element for high-resolution X-ray detection. The peak position of the quantum dot glass film quartz plate is at 530nm and the peak shape is sharp, and the relative luminous intensity is 100%. The peak position of the optical fiber imaging element for high-resolution X-ray detection is at 530nm and the peak shape is sharp, indicating that the luminous purity of the sample is high; the relative luminous intensity is 75%, and the luminous intensity is only lost by 25%, indicating that the luminous intensity of the sample is high. Using X-ray light as the light source to test the resolution of the optical fiber light cone in this embodiment is 50.8lp / mm, and the resolution of the optical fiber imaging element for high-resolution X-ray detection is 50.8lp / mm, indicating that there is no loss of resolution when filling quantum dot glass powder in the microporous structure.

[0095] Embodiment 3:

[0096] This embodiment provides a high-resolution X-ray detection optical fiber image transmission element, and its structural schematic diagram is shown in Figure 3 .

[0097] The difference between this embodiment and embodiment 1 is that the optical fiber image transmission element adopts an optical fiber image inverter with a core diameter of 10 μm and a thickness of 10 mm. Furthermore, the acid-washed optical fiber panel 4 in embodiment 1 is an acid-washed optical fiber image inverter 6 in this embodiment; the filled optical fiber panel in embodiment 1 is a filled optical fiber image inverter in this embodiment.

[0098] The X-ray emission spectrum of the quantum dot glass film quartz plate and the high-resolution X-ray detection optical fiber imaging element in this embodiment was tested using the emission spectrum under the action of X-rays at 50 kV and 10 μA. The test results are shown in Figure 2. Figure 6 As shown, A is the luminous intensity curve of the quantum dot glass film quartz plate, and B is the luminous intensity curve of the optical fiber imaging element for high-resolution X-ray detection. The peak position of the quantum dot glass film quartz plate is at 530nm and the peak shape is sharp, and the relative luminous intensity is 100%. The peak position of the optical fiber imaging element for high-resolution X-ray detection is at 530nm and the peak shape is sharp, indicating that the luminous purity of the sample is high; the relative luminous intensity is 62%, and the luminous intensity is only lost by 38%, indicating that the luminous intensity of the sample is high. Using X-ray light as the light source to test the resolution of the optical fiber image inverter in this embodiment is 50.8lp / mm, and the resolution of the optical fiber imaging element for high-resolution X-ray detection is 50.8lp / mm, indicating that there is no loss of resolution when filling quantum dot glass powder in the microporous structure.

[0099] Embodiment 4:

[0100] This embodiment provides a fiber optic imaging element for high-resolution X-ray detection and a method for preparing the same.

[0101] The difference between this embodiment and embodiment 1 is that the perovskite quantum dot glass in this embodiment is CsPbCl3 perovskite quantum dot glass with a fluorescent color of blue light. In terms of oxide mass percentage, the CsPbCl3 perovskite quantum dot glass ratio is 30% SiO2; 30% H3BO3; 20% ZnO; 10% Cs2CO3; 5% PbCl2; 5% NaCl. 10g of high-purity raw materials are fully mixed and melted in air at 1050°C for 12min to produce a uniform glass melt. The glass melt is then poured into a brass mold to obtain a precursor glass. Finally, the precursor glass is annealed at 400°C for 2h to induce in-situ growth of CsPbCl3 in the glass matrix to obtain CsPbCl3 perovskite quantum dot glass.

[0102] The X-ray emission spectrum of the quantum dot glass film quartz plate and the high-resolution X-ray detection optical fiber imaging element in this embodiment was tested using the emission spectrum under the action of X-rays at 50 kV and 10 μA. The test results are shown in Figure 2. Figure 7 As shown, A is the luminous intensity curve of the quantum dot glass film quartz plate, and B is the luminous intensity curve of the optical fiber imaging element for high-resolution X-ray detection. The peak position of the quantum dot glass film quartz plate is at 450nm and the peak shape is sharp, and the relative luminous intensity is 100%. The peak position of the optical fiber imaging element for high-resolution X-ray detection is at 450nm and the peak shape is sharp, indicating that the luminous purity of the sample is high; the relative luminous intensity is 80.2%, and the luminous intensity is only lost by 19.8%, indicating that the luminous intensity of the sample is high. Using X-ray light as the light source to test the resolution of the optical fiber image inverter in this embodiment is 50.8lp / mm, and the resolution of the optical fiber imaging element for high-resolution X-ray detection is 50.8lp / mm, indicating that there is no loss of resolution when filling the quantum dot glass powder in the microporous structure.

[0103] Embodiment 5:

[0104] This embodiment provides a fiber optic imaging element for high-resolution X-ray detection and a method for preparing the same.

[0105] The difference between this embodiment and embodiment 1 is that the perovskite quantum dot glass in this embodiment is CsPbI3 perovskite quantum dot glass with a fluorescent color of red light. In terms of oxide mass percentage, the ratio of CsPbI3 perovskite quantum dot glass is 30% SiO2; 30% H3BO3; 20% ZnO; 10% Cs2CO3; 5% PbI2; 5% NaI. 10g of high-purity raw materials are fully mixed and melted in air at 1050°C for 12min to produce a uniform glass melt. The glass melt is then poured into a brass mold to obtain a precursor glass. Finally, the CsPbI3 perovskite quantum dot glass is obtained by heating the precursor glass at 400°C for 2h to induce in-situ growth of CsPbI3 in the glass matrix.

[0106] The X-ray emission spectrum of the quantum dot glass film quartz plate and the high-resolution X-ray detection optical fiber imaging element in this embodiment was tested using the emission spectrum under the action of X-rays at 50 kV and 10 μA. The test results are shown in Figure 2. Figure 8 As shown, A is the luminous intensity curve of the quantum dot glass film quartz plate, and B is the luminous intensity curve of the optical fiber imaging element for high-resolution X-ray detection. The peak position of the quantum dot glass film quartz plate is at 630nm and the peak shape is sharp, and the relative luminous intensity is 100%. The peak position of the optical fiber imaging element for high-resolution X-ray detection is at 630nm and the peak shape is sharp, indicating that the luminous purity of the sample is high; the relative luminous intensity is 79.7%, and the luminous intensity is only lost by 20.3%, indicating that the luminous intensity of the sample is high. Using X-ray light as the light source to test the resolution of the optical fiber image inverter in this embodiment is 50.8lp / mm, and the resolution of the optical fiber imaging element for high-resolution X-ray detection is 50.8lp / mm, indicating that there is no loss of resolution when filling the quantum dot glass powder in the microporous structure.

[0107] Example 6

[0108] This embodiment provides a fiber optic imaging element for high-resolution X-ray detection and a method for preparing the same.

[0109] The difference between this embodiment and embodiment 1 is that in the optical fiber imaging element for high-resolution X-ray detection in this embodiment, the aluminum oxide and hafnium oxide composite film 2 is not plated on the filling surface of the filling optical fiber faceplate.

[0110] The fluorescence spectra of the quantum dot glass film quartz plate and the optical fiber imaging element for high-resolution X-ray detection in this embodiment are tested using a fluorescence spectrometer. The peak position of the quantum dot glass film quartz plate is at 530nm and the peak shape is sharp, and the relative luminous intensity is 100%. The peak position of the optical fiber imaging element for high-resolution X-ray detection is at 530nm and the peak shape is sharp, indicating that the luminous purity of the sample is high; the relative luminous intensity is 70%, and the luminous intensity is only lost by 30%, indicating that the luminous intensity of the sample is high. Using ultraviolet light as the light source to test the resolution of the optical fiber panel in this embodiment is 50.8lp / mm, and the resolution of the optical fiber imaging element for high-resolution X-ray detection is 50.8lp / mm, indicating that there is no loss of resolution when filling the quantum dot glass powder in the microporous structure.

[0111] Example 7

[0112] The difference between this embodiment and embodiment 1 is that when preparing the quantum dot glass film quartz plate and the optical fiber imaging element for high-resolution X-ray detection, the CsPbBr3 perovskite quantum dot glass powder is replaced with CdSe perovskite quantum dot glass powder.

[0113] The fluorescence spectra of the high-resolution X-ray detection optical fiber imaging element in Example 1 and the high-resolution X-ray detection optical fiber imaging element in this example were tested using a fluorescence spectrometer. The peak position of the high-resolution X-ray detection optical fiber imaging element in Example 1 was 530nm, and the peak shape was sharp, and the relative luminous intensity was 100%. The peak position of the high-resolution X-ray detection optical fiber imaging element in this example was 530nm, but the half-height width of the peak was larger than that of the former.

[0114] Comparative Example 1:

[0115] The optical fiber panel in Example 1 is used as a substrate, and a perovskite quantum dot glass film with a thickness of 100 μm is prepared on its surface to obtain a quantum dot glass film optical fiber imaging element. The specific method is: the perovskite quantum dot glass powder in Example 1 is dispersed in anhydrous ethanol to prepare a quantum dot dispersion liquid, 0.4 ml of the quantum dot dispersion liquid is dripped on the surface of the optical fiber panel, and the rotation speed is controlled to 500 rpm by spin coating, and the time is 60 s. After spin coating, it is heated in an oven at 60°C for 30 min, and repeated 3 times to form a quantum dot glass film with a thickness of 100 μm on the surface of the substrate.

[0116] The resolution of the quantum dot glass film optical fiber imaging element was tested using X-ray light as a light source, and the result showed 15 lp / mm. Compared with the high-resolution X-ray detection optical fiber imaging element in Example 1, its resolution is lower, indicating that the perovskite quantum dot glass powder filled in the microporous structure of the optical fiber panel can effectively improve the resolution.

[0117] The technical features in the claims and / or the specification of the present invention may be combined, and the combination is not limited to the combination obtained by reference in the claims. The technical solution obtained by combining the technical features in the claims and / or the specification is also within the protection scope of the present invention.

[0118] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A method for preparing an optical fiber imaging element for high-resolution X-ray detection, characterized in that: The steps include: Acid-washing is performed on a cross section of one end of an optical fiber imaging element to form a microporous structure at the cross section, wherein the depth of the microporous structure is 100 to 500 μm, thereby obtaining an acid-washed optical fiber imaging element; the core of the optical fiber imaging element is made of an acid-resistant material, and the cladding is made of an acid-resistant material; Filling the microporous structure with perovskite quantum dot glass powder to obtain a filled optical fiber imaging element; and, A protective layer is provided on the filling surface of the filled optical fiber imaging element to obtain an optical fiber imaging element for high-resolution X-ray detection.

2. The preparation method according to claim 1, characterized in that: The perovskite quantum dot glass powder is CsPbX3 perovskite quantum dot glass powder; wherein X is at least one of Cl, Br and I.

3. The preparation method according to claim 2, characterized in that: Measured in terms of oxide mass percentage, the components of the CsPbX3 perovskite quantum dot glass powder include: SiO2: 30-40%; H3BO3: 20-30%; ZnO: 15-20%; Cs2CO3: 10-15%; PbX2: 5-10%; and NaX: 5-10%.

4. The preparation method according to claim 3, characterized in that: The preparation method of the CsPbX3 perovskite quantum dot glass powder comprises the following steps: preparing glass raw materials, and melting the glass raw materials at 1000-1100° C. to obtain a glass melt; pouring the glass melt into a mold to obtain a precursor glass; The precursor glass is annealed at 350-450° C. for 2-3 hours to obtain CsPbX3 perovskite quantum dot glass; and The CsPbX3 perovskite quantum dot glass is ground into powder to obtain the CsPbX3 perovskite quantum dot glass powder.

5. The preparation method according to claim 1, characterized in that: The method of filling the perovskite quantum dot glass powder into the microporous structure comprises the following steps: a. dispersing the perovskite quantum dot glass powder in an organic solvent to obtain a quantum dot dispersion; b. immersing the microporous structure of the pickled optical fiber imaging element in the quantum dot dispersion, ultrasonically treating, then taking out the pickled optical fiber imaging element, scraping off the quantum dot dispersion at the surface without pores, and drying; Repeat step b multiple times until the perovskite quantum dot glass powder fully fills the microporous structure to obtain the filled optical fiber imaging element.

6. The preparation method according to claim 1, characterized in that: The size of the perovskite quantum dot glass powder is 100-200 nm.

7. The preparation method according to claim 1, characterized in that: The protective layer includes an anti-reflection film.

8. The preparation method according to claim 1, characterized in that: The protective layer comprises a quartz window, and the thickness of the quartz window is 2-3 mm.

9. A high-resolution X-ray detection optical fiber imaging element, characterized in that: It includes: An optical fiber imaging element, wherein the core of the optical fiber imaging element is made of an acid-resistant material, the cladding is made of an acid-resistant material, the core of the optical fiber imaging element is concave at a cross section at one end, and a microporous structure with a depth of 100 to 500 μm is formed at the cross section; Perovskite quantum dot glass powder, wherein the perovskite quantum dot glass powder is filled in the microporous structure; and A protective layer is provided on the cross section of the optical fiber imaging element filled with the perovskite quantum dot glass powder.

10. Application of the optical fiber imaging element for high-resolution X-ray detection according to claim 9 in the field of X-ray detection.

Citation Information

Patent Citations

  • Saturable absorber device, preparation method thereof and mode-locking fiber laser

    CN108767648A

  • Double-core composite material optical fiber probe, preparation method and double-parameter sensor based on probe

    CN116430432A

  • Multilayer reflector for high efficiency and high spatial resoution pixelated x-ray scintillators and fabrication method

    US20230367023A1

Cited By

  • High-resolution fiber optic image transmission element for x-ray detection, preparation method therefor and use thereof

    WO2026103066A1